Imaging of brain metastasis in non-small-cell lung cancer: indications, protocols, diagnosis, post-therapy imaging, and implications regarding management. Issue 3 (March 2023) - Chakrabarty, N.; Mahajan, A.; Patil, V.; Noronha, V.; Prabhash, K.
Abstract : Increased survival (due to the use of targeted therapies based on genomic profiling) has resulted in the increased incidence of brain metastasis during the course of disease, and thus, made it essential to have proper imaging guidelines in place for brain metastasis from non-small-cell lung cancer (NSCLC). Brain parenchymal metastases can have varied imaging appearances, and it is pertinent to be aware of the various molecular risk factors for brain metastasis from NSCLC along with their suggestive imaging appearances, so as to identify them early. Leptomeningeal metastasis requires additional imaging of the spine and an early cerebrospinal fluid (CSF) analysis. Differentiation of post-therapy change from recurrence on imaging has a bearing on the management, hence the need for its awareness. This article will provide in-depth literature review of the epidemiology, aetiopathogenesis, screening, detection, diagnosis, post-therapy imaging, and implications regarding the management of brain metastasis from NSCLC. In addition, we will also briefly highlight the role of artificial intelligence (AI) in brain metastasis screening.